Venlafaxine, an anti-depressant drug, induces apoptosis in MV3 human melanoma cells through JNK1/2-Nur77 signaling pathway - Niu, Ting; Wei, Zhiying; Fu, Jiao; Chen, Shu; Wang, Ru; Wang, Yuya; Zheng, Ruihe (Frontiers in Pharmacology, 2023)
Venlafaxine is one of the most commonly used anti-depressant and antineoplastic drug. Previous studies have predicted venlafaxine as an anti-cancer compound, but the therapeutic effects of venlafaxine in melanoma have not yet been demonstrated. Nur77 is an orphan nuclear receptor that highly expressed in melanoma cells and can interact with Bcl-2 to convert Bcl-2 from an antiapoptotic to a pro-apoptotic protein. Here, our data revealed that venlafaxine could reduce the growth, and induce apoptosis of melanoma cells through a Nur77-dependent way. Our results also showed that treatment with venlafaxine (20 mg/kg, i.p.) potently inhibited the growth of melanoma cells in nude mice. Mechanistically, venlafaxine activated JNK1/2 signaling, induced Nur77 expressions and mitochondrial localization, thereby promoting apoptosis of melanoma cells. Knockdown of Nur77 and JNK1/2, or inhibition of JNK1/2 signaling with its inhibitor SP600125 attenuated the anti-cancer effects of venlafaxine. In summary, our results suggested venlafaxine as a potential therapy for melanoma.